Matematización del centro de masa a partir de una aplicación en la ingeniería - Vija Suárez, Oscar Javier; Castellanos Ortegón, Ingrid Yurani (Revista Científica, 2011)
The understanding of concepts of physics are of prime importance in applied fields of this science, engineering is a field of vital importance for the development of society and the evolution of the same, its importance lies in the contribution this can generate industrial and technologically . In particular we find that there are difficulties in the conceptualization of the center of mass of a system, it is almost always associated with center of gravity. This paper is a didactic approach to teach the concept of center of mass student-generated physical-mathematical thinking to ensure a proper appropriation and utilization. The proposal is based on a process of evolution of images formed by the student named "mathematization", which focuses on the mathematics of physical interpretations, not as a simple algorithm development tool but as a necessary and sufficient to explain the phenomena of nature consistently.